Modelling the impacts of climate change on hydrology and water resources in the Niger-South Sub-Catchment of the Niger River Basin, Nigeria - Johnson, Oloruntade Ajayi (2017)
The Niger River Basin (NRB), located between latitudes 4–7.5o N and longitudes 4.5– 7o E, is a trans-boundary basin which transverses about nine countries of West and Central Africa with a total active area of about 925,796 km2, of which about 60% is an agricultural rain-fed and irrigated area. In addition, various hydropower stations are currently in operation along the course of the main river. Hence, there is a growing concern that any unfavourable climate change impact in the basin might have consequential impacts on the socioeconomic lives of the people of the country. To assess these possible impacts of future climate change on the water resources in the NRB, a sub-catchment of the Nigerian part, hereafter referred to as Niger-South Basin (NSB) is chosen in the present study. Statistical, trend and drought analyses were performed on some hydro-climatic variables to ascertain the direction of change in climate and as well the occurrence of drought with a view to evaluating the likely impacts on hydrology and water resources in the basin. The results showed a relatively uniform increase in warming and drying over the entire landscape (1948-2008). While the decade 2000s and year 1983 were the driest, average annual rainfall was dominated by August (15%), with the summer season (June, July and August; JJA) also contributing the highest (40%). Although, only 15% was significant (α < 0.1) , rainfall trend was generally negative, with about 8 months exhibiting downward trend, while only JJA showed significant upward trend. Similarly, warming over the basin was relatively uniform; while the period between 1978 and 1979, and year 1998 were the warmest (mean temperature = 27.8 oC), the warmest season was in spring (March, April and May). Significant increasing trends were observed for all series (minimum; TMIN, maximum; TMAX and mean temperature; TMEAN) and on monthly, seasonal and annual bases, but trends were strongest in TMIN and in autumn. However, average warming over the entire landscape was 0.83 oC per annum. Drought analysis indicated pockets of wet and dry conditions of varied severities since 1970, with meteorological droughts observed during 1973 to 1977 and 1982-1984, while the decade 1980s showed between moderate and extreme droughts. Increased warming influenced hydrological drought, especially during the 1990s, given the relatively higher correlation between the Standardised Precipitation Evapotranspiration Index (SPEI) and the Standardised Runoff Index (SRI), while a strong 2-year periodic power was found during the late 1970s and early 1980 controlling drought. Although a moderately wet basin has been observed, with increased warming, a reversal of the situation might be experienced in the future. For the hydrological modelling, a hydrological model, Soil and Water Assessment Tool (SWAT) was set up to evaluate the impacts of the likely future climate change on the hydrology and water resources in the NSB. Calibration and validation of the model was done using the discharge data for the period 1980-1989 and 1990-1999, respectively. With Nash-Sutcliffe (NS) of 0.82 (calibration) and 0.73 (validation), the model indicated good performance and robustness. Thereafter, five bias-corrected General Circulation Models (GCMs) (CNRM, GFDL, CCCma, ICHEC and NCC) were downscaled and used to drive the model for the future (2040-2059 and 2070- 2089) hydrological parameters simulations. The results showed declines in average annual precipitation, runoff, baseflow, streamflow and potential evapotranspiration (PET) of about 16%, 65%, 2%, 23% and 1.7%, respectively during the mid-century (2040-2059), and 14%, 60%, 0.3%, 20% and 0.8% for precipitation, runoff, baseflow, streamflow and PET during the late-century (2070-2089). Notwithstanding the uncertainty observed during the study, the results showed that the basin is highly sensitive to climate change. Therefore, adoption of good water resources management and adaptation strategies are needed to ensure sustainable water supply in the basin especially during the mid-century.